Murder, plainly read - Alan, Isabella (Alan, Isabella. Amish quilt shop mystery, 2015)
When Old Order Bishop Bartholomew Belier is found dead in the bookmobile of Austina Shaker, the librarian he vowed to ruin, Angie and her quilting circle set out to prove Austina's innocence before the killer strikes again.